1985
DOI: 10.1152/ajpgi.1985.249.5.g580
|View full text |Cite
|
Sign up to set email alerts
|

Relation between antral motility and gastric emptying of solids and liquids in humans

Abstract: Our aim was to test the hypothesis that there is a relation between antral phasic pressure activity and the emptying of solids and liquids from the intact human stomach after a mixed meal. This hypothesis was evaluated in 14 healthy individuals in whom we performed simultaneous antral manometry and radioscintigraphy after ingestion of a meal labeled with [99mTc]sulfur colloid in cooked egg (solid component) and [111In]DTPA (liquid component). Analysis of the data included an in-depth evaluation of different mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
199
4
5

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(229 citation statements)
references
References 10 publications
11
199
4
5
Order By: Relevance
“…The results of the present study show that 10 mg ICS 205-930 had virtually no effect on gastric emptying, whereas after 20 mg ICS 205-930, (Camilleri et al, 1985;Houghton et al, 1986) but also of liquid (Stemper & Cooke, 1975;Weisbrodt et al, 1969) and semisolid meals (Stacher et al, 1984(Stacher et al, , 1987. The frequency and the propagation velocity of antral contractions were influenced by ICS 205-930 but to a minor degree.…”
Section: Discussioncontrasting
confidence: 41%
“…The results of the present study show that 10 mg ICS 205-930 had virtually no effect on gastric emptying, whereas after 20 mg ICS 205-930, (Camilleri et al, 1985;Houghton et al, 1986) but also of liquid (Stemper & Cooke, 1975;Weisbrodt et al, 1969) and semisolid meals (Stacher et al, 1984(Stacher et al, , 1987. The frequency and the propagation velocity of antral contractions were influenced by ICS 205-930 but to a minor degree.…”
Section: Discussioncontrasting
confidence: 41%
“…Among them, gastric antral motility is regarded as one of the main regulators of gastric emptying of solid meals [15]. A previous report described that emptying rates for the entire gastric contents are correlated with antral motor activity during the active emptying phase for solids in humans [4]. We adopted the 13 C-octanoic acid breath test as a comparative test because this method correlates with a gold standard of gastric emptying, scintigraphy, in humans [6].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies demonstrated the importance of gastric antral contractility to the normal emptying of solids [19]. Reduced antral motility is associated with retardation of gastric emptying with prolongation of the lag time and gastric emptying half-time (T 1/2 ), and a slower post-lag gastric emptying phase [20].…”
Section: Discussionmentioning
confidence: 99%